2009
DOI: 10.1007/s10560-009-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attachment Among Korean–American Adolescents

Abstract: The present study examined the relationship between parental care and control perceived by Korean-American adolescents, and further investigated the relationships between parental attachment styles and mental health measures including self-esteem, depression, and social support. The relationship between parental care and parental control resulted in a significantly negative correlation. Parental care showed significantly positive correlations with self-esteem and social support, and a negative correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Korean American parental acceptance-rejection and control have been identified as two important factors that significantly influence their offspring's mental health. Korean American adolescents' perceived low parental acceptance-rejection and intergenerational conflicts were found to significantly influence their depressed mood (E. Kim & Cain, 2008;Park, 2009). Korean American parental acceptancerejection was also found to significantly influence their adolescents' psychological problems (E. Kim, 2008b) and their children's social competence (E. Kim, Han, & McCubbin, 2007).…”
Section: Korean American Parental Acceptance-rejection and Controlmentioning
confidence: 97%
“…Korean American parental acceptance-rejection and control have been identified as two important factors that significantly influence their offspring's mental health. Korean American adolescents' perceived low parental acceptance-rejection and intergenerational conflicts were found to significantly influence their depressed mood (E. Kim & Cain, 2008;Park, 2009). Korean American parental acceptancerejection was also found to significantly influence their adolescents' psychological problems (E. Kim, 2008b) and their children's social competence (E. Kim, Han, & McCubbin, 2007).…”
Section: Korean American Parental Acceptance-rejection and Controlmentioning
confidence: 97%
“…88 Juang and Cookston found that higher levels of family obligation were associated with fewer depressive symptoms among Chinese American adolescents; increasing family obligation behaviors were associated with decreasing depressive symptoms over time. 89 Park (2009) found that parental care is negatively associated with depression among Korean adolescents, 90 and Qin et al found that family cohesion is protective of depression among Chinese adolescents. 68 According to Willgerodt et al, family bonds had a significant negative effect on emotional distress (depression) over time among Filipinos and Chinese adolescents, 91 and Wong found that positive peer and parent relationships were associated with lower depression levels among Chinese and Southeast Asians.…”
Section: Question 4: What Protective Factors Exist To Buffer the Effementioning
confidence: 99%
“…According to Dwairy (2010), perceived control from the father was related to psychological problems in western culture. In another study reported that a significant relationship between depression and perceived control from the mother (Park, 2009). However, the perceived control from father was not found to be significant predictor of any psychological problem in this study.…”
Section: Discussionmentioning
confidence: 97%